Identification of Core Competencies for Managing Farmer Producer Organizations Using Factor Analysis - Kumari, Neha; Bisht, Kamini (Indian Journal of Extension Education, 2023)
The study was conducted to identify core competencies essential for efficient management of Farmer Producer Organizations (FPOs) and their contribution to performance of FPOs in the national capital region of Delhi during 2021. Using random sampling procedure, data were collected from 80 farmer-directors from twelve FPOs in six districts of Delhi, Haryana and Uttar Pradesh in NCR of Delhi. Since directors of FPOs were found to lack managerial capabilities, they were exposed to several training programmes on how to manage their FPOs efficiently. But gaining knowledge and skills may not reflect in the competencies of trained farmers. Competency being the ability to apply knowledge and skill in accomplishing a task successfully, to measure the degree of competency possessed by directors of FPOs, a competency inventory was developed. The data were subjected to factor analysis to arrive at significant core competencies vital for success of FPOs. The factor analysis could confirm that six core competencies as indispensable for managing producer companies were; competencies for planning and business development, marketing management, controlling operations, financial management, democratic leadership, and managing business operations. Out of these, four competencies were found to significantly contribute to the performance of FPOs.
Keywords: FPO; Core managerial competencies; Competency inventory; Factor analysis NCR of Delhi